2019
DOI: 10.3390/genes10080591
|View full text |Cite
|
Sign up to set email alerts
|

Joint RNA-Seq and miRNA Profiling Analyses to Reveal Molecular Mechanisms in Regulating Thickness of Pod Canopy in Brassica napus

Abstract: Oilseed rape (Brassica napus) is the second largest oilseed crop worldwide. As an architecture component of B. napus, thickness of pod canopy (TPC) plays an important role in yield formation, especially under high-density cultivation conditions. However, the mechanisms underlying the regulation of TPC remain unclear. RNA and microRNA (miRNA) profiling of two groups of B. napus lines with significantly different TPC at the bolting with a tiny bud stage revealed differential expressions of numerous genes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 91 publications
2
13
0
Order By: Relevance
“…Increased methylation in the promoter region of a gene inhibits gene expression, while demethylation in the promoter region of a gene promotes gene expression [39]. We combined the current results with our previously reported transcriptome data [1] and identi ed 26 genes in the high-TPC materials that were signi cantly hypermethylated in their promoter regions compared to the low-TPC materials in B. napus ower buds, resulting in signi cant decreases in their expression ( Fig. 11A and Supplementary Table 1).…”
Section: Dmrs In Promoters Underlie Differences In Gene Expression Besupporting
confidence: 56%
See 3 more Smart Citations
“…Increased methylation in the promoter region of a gene inhibits gene expression, while demethylation in the promoter region of a gene promotes gene expression [39]. We combined the current results with our previously reported transcriptome data [1] and identi ed 26 genes in the high-TPC materials that were signi cantly hypermethylated in their promoter regions compared to the low-TPC materials in B. napus ower buds, resulting in signi cant decreases in their expression ( Fig. 11A and Supplementary Table 1).…”
Section: Dmrs In Promoters Underlie Differences In Gene Expression Besupporting
confidence: 56%
“…GWAS identi ed four, ve, and seven SNPs for FEBH, FEBN, and PH, respectively, in B. napus and uncovered many genes associated with these traits [5]. We recently reported that TPC is regulated by miRNAs and identi ed many candidate genes for TPC based on RNA-Seq and miRNA pro ling analyses [1]. Many genes involved in nitrogen-related responses were dramatically differentially expressed in high-vs. low-TPC lines, such as ASP5, ASP2, ASN3, ATCYSC1, PAL2, APT2, CRTISO, and COX15 [1], suggesting that nitrogen metabolism plays important roles in regulating TPC in B. napus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant height was measured using a standard ruler (30 cm) placed vertically from the tallest point of the canopy of an in orescence (if owering) or from the tallest leaf (if non owering) to the soil line (base of the plant). In orescence length was measured from the bracts to the top of the plant [51]. The color of each leaf, ower ray oret (petals) and disc oret were determined using the Royal Horticultural Society [24] chart with the visual appearance under natural sunlight in the greenhouse.…”
Section: Methodsmentioning
confidence: 99%